Repeated intestinal perforations in vascular Ehlers-Danlos syndrome: a case report of a novel mutation in the COL3A1 gene - Taichi Horino; Yuji Miyamoto; Mayuko Ohuchi; Katsuhiro Ogawa; Naoya Yoshida; Takatoshi Ishiko; Chieko Kukinaka; Rumi Sasaki; Takashi Ohba; Hideo Baba (Surgical Case Reports, 2023)
Abstract Background Ehlers-Danlos syndrome is an inherited connective-tissue disorder characterized by skin hyperextensibility, joint hypermobility, and tissue fragility. Intestinal perforation is one of the fatal manifestations of this syndrome, and its management is complicated. Case presentation A 58-year-old woman with a familial history of Ehlers-Danlos syndrome visited the emergency department due to a sudden onset of lower abdominal pain. Plain abdominal computed tomography showed abdominal free air. We found a perforated descending colon and subsequently resected this lesion and performed ileostomy. Fifty-one days after this first operation, the patient had transverse colon perforation and thus underwent the Hartmann procedure as the second operation. In addition, she was diagnosed with small bowel perforation 53 days after the first operation and consequently underwent a third operation—partial resection of the jejunum with functional end-to-end anastomosis. Fifty-eight days after the first operation, she complained of acute abdominal pain. Plain abdominal computed tomography showed fluid collection near the jejunojejunal anastomosis. We detected dehiscence at the entry hole of the linear stapler during the operation and thus performed partial resection of the affected jejunum, followed by jejunostomy. The postoperative course of the fourth operation was uneventful. Genetic testing revealed a novel missense mutation (c.2095G>T, p.Gly699Cys) in the COL3A1 gene, which is presumed to be a pathogenic variant of vascular Ehlers-Danlos syndrome. Conclusion Vascular Ehlers-Danlos syndrome should be considered in the case of repeated intestinal perforation. The identified missense mutation in the COL3A1 gene (c.2095G>T, p.Gly699Cys) might be a novel pathogenic variation causing vascular Ehlers-Danlos syndrome. Careful postoperative screening and multidisciplinary management are required.